Early-age performance of lag screw shear connections for glulam-lightweight concrete composite beams. (1st October 2017) - Jiang, Yuchen; Hong, Wan; Hu, Xiamin; Crocetti, Roberto; Wang, Lei; Sun, Weimin
Highlights: Early-age performance of screw connections was experimentally investigated. Stiffness and strength of screw connections increase rapidly with time before 7 days. Properties of glulam and screw are decisive when concrete hardens to some degree. Models to predict the early-age performance of screw connections are proposed. Abstract: Mechanical behavior of the shear connections has a significant influence on both the load-carrying capacity and the bending stiffness of timber-concrete composite (TCC) beams. All the studies reported so far have concentrated on the performance of TCC connections in mature concrete. The performance of shear connections for TCC beams at early concrete ages, however, has not been investigated yet. This information is essential to evaluate the structural behavior of TCC floors or bridges during construction. In this paper, a total of 18 push-out tests with concrete ages ranging from 12 h to 28 days are performed, to investigate the early-age performance of lag screw shear connections in the lightweight concrete. Development of concrete strength with time is also analyzed. At the concrete ages shorter than 7 days, both the stiffness and strength of the screw connectors increase evidently with time, which follows the same growth trend with the concrete strength. After a 7-day cure, screw shear connections reach almost 100% of both the 28-day serviceability slip modulus and shear strength. Material properties of the glulam and the screw fastener are decisive in the shear performance of connections when the concrete hardens to some degree. Based on the experimental results, the accuracy of the design methods proposed in Eurocode 5 is evaluated. In addition, by non-linear regression of the experiment data, expressions to predict the development of load-carrying capacity and serviceability slip modulus for screw shear connections before 28 days are established.